Implementasi Kebijakan Keterbukaan Akses Data Perbankan Dalam Meningkatkan Tax Compliance Di Indonesia - Lutfia Rizkyatul Akbar; Gunadi Gunadi (Jurnal Akuntansi dan Governance, 2021)
This study aims to assess the implementation of the openness of banking data access policies to improving tax compliance in Indonesia. It cause by the implementation of tax collection using a self-assessment system, thus requiring taxpayer data and information through financial institutions, include banking. Researchers used qualitative descriptive methods. The results of this study are, first, there is support for the implementation of the policy on openness to access to banking data in increasing tax compliance in Indonesia in the form of the issuance of Law Number 9 of 2017 concerning Access to Financial Information. Second, the implementation of banking data disclosure policies to increase tax compliance in Indonesia, including the willingness of target groups to comply with policy outputs, in this case the reporting of customer data by banks to the DGT. Third, the policy of open banking data access does not impede or reduce the number of bank accounts and deposits. Fourth, there are technical obstacles both by the DGT and the banking sector, especially in the first year. Furthermore, there are several inhibiting factors in the implementation of this policy, namely IT factors, and resistance from some circles at the beginning of the emergence of regulations, limited financial resources to process data quickly, so it must be done gradually, in addition to lack of quantity and quality of human resources